Does the assumption on innovation process play an important role for filtered historical simulation model? - Emrah Altun; Huseyin Tatlidil; Gamze Ozel; Saralees Nadarajah (Journal of Risk and Financial Management, 2018)
Most of the financial institutions compute the Value-at-Risk (VaR) of their trading portfolios using historical simulation-based methods. In this paper, we examine the Filtered Historical Simulation (FHS) model introduced by Barone-Adesi et al. (1999) theoretically and empirically. The main goal of this study is to find an answer for the following question: 'Does the assumption on innovation process play an important role for the Filtered Historical Simulation model?'. For this goal, we investigate the performance of FHS model with skewed and fat-tailed innovations distributions such as normal, skew normal, Student's-t, skew-T, generalized error, and skewed generalized error distributions. The performances of FHS models are evaluated by means of unconditional and conditional likelihood ratio tests and loss functions. Based on the empirical results, we conclude that the FHS models with generalized error and skew-T distributions produce more accurate VaR forecasts.
Keywords: 330; Filtered Historical Simulation Model; Value-at-Risk; volatility; backtesting